Quantitative relationships between sensitizing dose of DNCB and reactivity in normal subjects. - Friedmann, P S (1983)
We have developed quantitative methods which enable us to measure susceptibility to sensitization with dinitrochlorobenzene (DNBC) and the degree of responsiveness of groups, and to analyse factors affecting the afferent and efferent components of the response. Five groups of normal subjects (132 individuals) were sensitized with DNCB (1,000, 500, 250, 125 or 62.5 micrograms). One month later, each subject was challenged with 12.5, 6.25 and 3.125 micrograms of DNCB on standard patch test felts. After 48 h the reaction at each challenge site was graded clinically and measured as diameter of induration and increase in skinfold thickness. The proportion of subjects sensitized increased with sensitizing dose; 8% were sensitized by 62.5 and 100% were sensitized by 500 micrograms or more. The 50% sensitizing dose (ED50) was calculated as 116 micrograms. Increase in skinfold thickness proved the best method of assessing response and was linearly related to log challenge dose. There was also a linear relationship between degree of sensitivity and log sensitizing dose so that, on average, each time sensitizing dose was halved, the challenge dose required to produce the same response increased 1.5-fold. These methods can be used to measure sensitizability of a population, the degree of sensitivity and the expression of reactivity. The technique will allow quantitative study of factors altering the induction or expression of such reactivity in disease.